Biochemical and isoenzyme analyses of elephant grass, Pennisetum purpureum (Schum) varieties Análises bioquímicas e isoenzímicas de variedades de capim elefante Pennisetum purpureum (Schum) - E.E. Bach; V.B.G. Alcântara; P.B. Alcântara; E.A. Veasey (Scientia Agricola, 1995)
This study characterized seven Pennisetum purpureum varieties, namely v. Anão, Bajra, Cameroon, Guaçu, Roxo, Taiwan A-144 and Uruckwami, through biochemical analyses, including protein, glucose and fructose contents, and polyacrylamide gel electrophoresis using the esterase system, by sampling 30, 60, 90, 120 and 150 day-old leaves. The number of nodes per stem and the percentage of bud emergence were also recorded. Variety Taiwan A-144 presented the highest number of nodes per stem and percentage of emerging buds. Protein concentration decreased gradually after 60 days for all varieties, except for Anão. Variety Guaçu presented the highest level of glucose in 90 day-old plants, whereas Cameroon presented the highest levels at 120 and 150 days. The esterase band patterns changed with plant age for all varieties, showing a tendency to increase the number of bands with time. The best age for discriminating between esterase bands of P. purpureum varieties was at 120 days, when most variation could be observed. Foram analisadas sete variedades de P. purpureum, tais como: Anão, Bajra, Cameroon, Guaçu, Roxo, Taiwan A-144 e Uruckwami, através de testes bioquímicos determinando a concentração de proteínas, glicose e frutose, além de observar, através de gel de eletroforese, as bandas de esterase. Os extratos protéicos foram preparados amostrando-se folhas com 30, 60, 90, 120 e 150 dias. Os números de nós por colmo e a porcentagem de brotamento das gemas foram também avaliados. A variedade Taiwan A-144 apresentou o maior número de nós por colmo e porcentagem de brotamento das gemas. Com relação à concentração de proteínas, esta decresceu gradualmente após 60 dias para todas as variedades, com exceção da Anão. A maior concentração de glicose foi apresentada pela variedade Guaçu aos 90 dias e pela Cameroon aos 120 e 150 dias. Os padrões eletroforéticos da esterase se alteraram com a idade da planta para todas as variedades, mostrando tendência a aumentar o número de bandas com o tempo. A melhor idade para discriminar as variedades de capim elefante foi aos 120 dias, onde foi encontrada maior variação.